Gambaran Social Skills Mahasiswa dengan Bipolar Disorder - Nadia Khairina; Fritamarcelin Baranandita Asriliantya (Universitas Negeri Malang, 2024)
Social skills are indispensable in building social relationships between people. Because social relationships are a fundamental indicator of social beings. This study aims to find out the picture of students who experience bipolar disorder, solutions in overcoming it, and the influence on their social behavior relationships in the campus environment. This study has criteria in determining the subject or participant of the research, namely at least 18 years old, diagnosed bipolar, and having the status of a student. The research uses qualitative research methods, with data collection in the form of literature studies and interviews with FS participants and validity using method triangulation techniques and source triangulation. As well as to analyze the data that has been collected using qualitative content analysis techniques. Based on interviews and observations show that individuals with bipolar disorder show changes in their social interactions in the campus environment when bipolar appears, and experience obstacles in improving their social skills so that they tend to stay away from their social environment. This study also shows a strong indication if individuals with bipolar disorder have a desire to harm themselves (self-harm). AbstrakKeterampilan sosial sangat diperlukan dalam membangun hubungan sosial antar manusia. Disebabkan hubungan sosial merupakan indikator fundamental sebagai makhluk sosial. Penelitian ini bertujuan untuk mengetahui gambaran mahasiswa yang mengalami kondisi gangguan bipolar, solusi dalam mengatasi tersebut, dan pengaruh bagi hubungan perilaku sosialnya dalam lingkungan kampus. Penelitian ini memiliki kriteria dalam menentukan subjek atau partisipan penelitian, yaiu berusia minimal 18 tahun, terdiagnosis bipolar, serta berstatus sebagai mahasiswa. Adapun penelitian menggunakan metode penelitian kualitatif, dengan pengumpulan data berupa studi literatur dan wawancara kepada partisipan FS dan melakukan validitas menggunakan teknik triangulasi metode dan triangulasi sumber. Serta untuk menganalisis data yang telah terkumpul menggunakan teknik analisis isi kualitatif. Berdasarkan wawancara dan observasi menunjukkan bahwa individu dengan kondisi gangguan bipolar menunjukan perubahan interaksi sosialnya di lingkungan kampus pada saat bipolar itu muncul, serta mengalami hambatan dalam meningkatkan keterampilan sosialya sehingga cenderung menjauh dari lingkungan sosialnya. Dalam penelitian ini juga memperlihatkan indikasi yang kuat jika individu yang mengalami gangguan bipolar memiliki keinginan untuk melukai dirinya sendiri (self-harm).